ANALISIS HASIL PENGUJIAN DAN KALIBRASI PARAMETER BLOOD PRESSURE PADA ALAT KESEHATAN BLOOD PRESSURE MONITOR - Nur Hadziqoh; Yeni Pertiwi; Romi Mulyadi (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Testing and calibration of medical devices are one of the efforts to ensure the quality of medical devices. Tests and calibrations have been carried out on the Blood Pressure Monitor (BPM) in the emergency room at one hospital. In this article, it will be explained how the stages in testing and calibrating the BPM tool are to get the results of the appropriate/unfit for the tool. It aims to provide knowledge and awareness to health workers as device users and patients on the implementation and importance of testing and calibration of medical devices. The method used is the Work Method from the Ministry of Health of the Republic of Indonesia in 2018. The test parameters consist of a physical examination test and the function of the tool as well as a Blood Pressure performance test at the systole pressure measurement points of 60, 80, 100, 120, 150, 200 mmHg and the diastole pressure point 30, 50, 65, 80, 100, and 150 mm Hg. The results of the physical examination and function tests were 100% good. The results of the blood pressure performance test 94% passed the test with the measurement uncertainty value below the tolerance threshold (± 5 mmHg). The 150 mmHg diastolic pressure measurement point has a measurement uncertainty value that exceeds the tolerance threshold so that the pressure point does not pass the test. Thus, the BPM medical device is declared suitable for use.